1996
DOI: 10.1006/viro.1996.0131
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Cleavage Site Recognized by the Turnip Yellow Mosaic Virus Protease

Abstract: The noncapsid protein expressed from ORF-206 of turnip yellow mosaic virus (TYMV) is autocatalytically processed by a papain-like protease, producing N-terminal 150-kDa and C-terminal 70-kDa proteins. By introducing two methionine residues near the N-terminus of the 70-kDa protein, we have obtained N-terminal amino acid sequence of that protein produced from [35S]methionine-labeled in vitro translations. The introduction of methionine residues was demonstrated to not interfere with viral replication or proteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
0
25
0
2
Order By: Relevance
“…1). First, a stop codon was introduced at amino acid 1259 of the 206K ORF, i.e., at the C terminus of the 140K protein (5,30). This stop codon was followed by a 494-nt deletion (nt 3872 to 4366 of the TYMV genome), the region that formerly encoded the first 165 amino acids of the 66K protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). First, a stop codon was introduced at amino acid 1259 of the 206K ORF, i.e., at the C terminus of the 140K protein (5,30). This stop codon was followed by a 494-nt deletion (nt 3872 to 4366 of the TYMV genome), the region that formerly encoded the first 165 amino acids of the 66K protein.…”
Section: Resultsmentioning
confidence: 99%
“…This large nonstructural protein also contains a papain-like cysteine proteinase domain located between the methyltransferase and the NTPase/helicase domains (54) that is responsible for the cotranslational proteolytic cleavage of the 206K protein in vitro (6,43). Mapping of the cleavage site (between A1259 and T1260) revealed that the resulting N-terminal protein product of 140 kDa (140K) contains the methyltransferase, proteinase, and NTPase/helicase motifs, whereas the C-terminal 66K protein encompasses the RdRp domain (5,30). This cleavage was also demonstrated to be functional in vivo (50), and both the 140K and 66K viral proteins appear to be essential for the replication of TYMV RNA genome (65).…”
mentioning
confidence: 99%
“…These regions of the RP gene contain the conserved methyltransferase and polymerase functional domains with signatures typical of the tymoviruses, which may explain their lower variability across species due to functional constrains [39]. In TYMV it has been demonstrated that the RP polyprotein is autocatalytically cleaved by the papainelike protease, yielding two replication-associated proteins of 140 kDa, containing the methyltransferase, the protease and the helicase domains, and 66 kDa, comprising the RNA-dependent RNA polymerase domains [40]. One cysteine and one histidine within the RP papaine-like domain are the putative active site residues [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In TYMV it has been demonstrated that the RP polyprotein is autocatalytically cleaved by the papainelike protease, yielding two replication-associated proteins of 140 kDa, containing the methyltransferase, the protease and the helicase domains, and 66 kDa, comprising the RNA-dependent RNA polymerase domains [40]. One cysteine and one histidine within the RP papaine-like domain are the putative active site residues [40,41]. These two residues were located also in the RP gene of ChiYMV, which strongly suggest that a similar mechanism of polyprotein processing is operating in this virus.…”
Section: Discussionmentioning
confidence: 99%
“…The methyltransferase and proteinase enzymatic modules are separated by an ϳ200-amino-acid-long proline-rich sequence with a predicted nonregular secondary structure (36) that may constitute a hinge between these two domains. The papain-like cysteine proteinase is responsible for the proteolytic cleavage of the 206K protein in vitro (6,41), leading to the synthesis of a 140-kDa N-terminal protein product (140K) containing the methyltransferase, proteinase, and NTPase/helicase domains and a 66-kDa C-terminal protein product (66K) encompassing the RdRp domain (5,26) (Fig. 1A).…”
mentioning
confidence: 99%